EID AL-FITR INFLUENCES THE NUMBER OF TRAIN PASSENGERS ON THE SUMATRA ISLAND (CALENDAR VARIATIONS TIME SERIES MODEL) - Akbar, Muhammad Sjahid; Safira, Dinda Ayu; Fadhilah, Rahmi; Damayanti, Salma; Riskianto, Riskianto; Puthy, Khem (PATTIMURA UNIVERSITY, 2024)
The Train is one of the transportation options for land travel on the island of Sumatra because of its affordable cost, comfort, and fast mobility. The majority of the population of Sumatra Island who are Muslims influenced the sharp increase in the number of train passengers during Eid Al-Fitr due to the large number of residents who returned to their hometowns (Sumatra Island). The time of Eid Al-Fitr will change every year on the Gregorian calendar, but it is always the same if using the Hijri calendar. This study aims to predict the number of train passengers on the island of Sumatra based on calendar variations (Eid Al-Fitr). To overcome this calendar variation, time series modeling will be used with the addition of exogenous variables (ARIMAX). This model consists of a time series regression equation added with a time series model of the residual regression equation of an exogenous variable. The resulting model can forecast the number of train passengers in the next few months and find that Eid Al-Fitr affects the data. Every Eid Al-Fitr, there is an increase in the number of train passengers by 49 passengers. The model obtained is in the good category with MAPE in-sample of 18.12% and out-sample of 9.93%.